Pengaruh Integritas Kelompok Terhadap Kinerja Pegawai Sekretariat Daerah Kabupaten Kapuas Hulu, Kalimantan Barat - Husni Syahrudin; Munawar Thoharudin (JEMBATAN, 2020)
Not achieving the performance targets that have been set are caused by many factors, both individual, group, organization both internal and external. The purpose of this study is to reveal how the influence of group integrity factors on the performance of employees at the Kapuas Hulu district secretariat. The research method used is a survey method with a quantitative approach. The population in this study were all employees (civil servant status) who worked at the regional secretariat of Kapuas Hulu Regency, totaling 137 employees. The sampling technique is done by using the Simple Random Sampling technique by determining the sample of respondents randomly. Based on the results of calculations with the formula, the sample in this study amounted to 102 employees. Data collection tools used closed questionnaire with 5 (five) interval scale answer options. The instrument testing uses validity and reliability tests. Prerequisite testing with residual normality test and linearity regression test. Data analysis in this study was carried out using statistical descriptive and inferential statistical analysis techniques. Based on the results of the study concluded that group integrity had a significant positive effect on employee performance